Probing the Protein-Protein Interactions of the FOXP1, FOXP2 and FOXP3 Forkhead Domains - Mhlongo, Paulina (University of the Witwatersrand, Johannesburg, 2023)
The FOXP proteins are classified amongst the forkhead box superfamily of transcription factors due to their highly conserved forkhead winged-helix domain (FHD). It is through this domain that FOX transcription factors are able to bind DNA in order to perform crucial roles in the regulation of gene transcription from development through adulthood. The FHD of FOXP1, FOXP2 and FOXP3 is remarkably unique in its ability to establish domain-swapped dimerization, postulated to drive interchromosomal interactions to regulate the transcription of distal genetic material. The FOXP1 and FOXP2 proteins are co-expressed and have also been demonstrated to directly interact in vivo and in vitro via a domain upstream of the FHD. Similarly, the FOXP1 and FOXP3 proteins have been established to form direct heterotypic interactions to function in regulatory T-cells (Treg). Provided that the FOXP FHD has the exceptional capability for dimerization, the study of the heterodimerization of the FHDs of these FOXP transcription factors may provide insight into the role of FHD-dimerization and its importance in the physiological roles of these proteins. Therefore, the aim of this work was to investigate whether a FOXP FHD heterodimerization event can occur between the FOXP1 and FOXP2 FHDs as well as between the FOXP1 and FOXP3 FHDs. The three FHD proteins were expressed and isolated for downstream interaction studies. The activity of the purified FHDs was studied using basic electrophoretic mobility shift assay. Their secondary and tertiary structures were characterized with circular dichroism and intrinsic fluorescence spectroscopies. Concentration-dependent size exclusion chromatography was employed to study their propensity for dimerization and fluorescence anisotropy was used to investigate both the homo and heterodimerization of the FHDs. It was revealed that FOXP3 FHD showed the highest propensity to homodimerize, whilst FOXP2 FHD showed the weakest propensity. Despite this, the homodimers of FOXP1 FHD appear to be less stable than that of the FOXP2 FHD. The heterodimerization studies suggest that FOXP1 FHD has preference in forming heterotypic associations with FOXP3 FHD rather than FOXP2 FHD.
Dissertation submitted in fulfilment of the requirements for the degree Master of Science to the Faculty of Science, School of Molecular and Cell Biology, at the University of the Witwatersrand, Johannesburg, 2023.
Keywords: Protein-protein interactions; Forkhead domain; FOXP1; FOXP2; FOXP3; UCTD; SDG-3: Good health and well-being